The Power of Empowerment: Predictors and Benefits of Shared Leadership in Organizations - Edelmann, Charlotte M.; Boen, Filip; Fransen, Katrien (Frontiers in Psychology, 2020)
Leadership plays an essential part in creating competitive advantage and well-being among employees. One way in which formal leaders can deal with the variety in responsibilities that comes with their role, is to share their responsibilities with team members (i.e., shared leadership). Although there is abundant literature on how high-quality peer leadership benefits team effectiveness and well-being, there is only limited evidence about the underpinning mechanisms of these relationships and how the formal leader can support this process. To address this lacuna, we conducted an online survey study with 146 employees from various organizations. The results suggest that an empowering leadership style of the formal leader is associated with higher perceived peer leadership quality on four different leadership roles (i.e., task, motivational, social, and external leader). In addition, formal leaders who empower their team members are also perceived as better leaders themselves. Moreover, the improved peer leadership quality was in turn positively related to team effectiveness and work satisfaction, while being negatively related to burnout. In line with the Social Identity Approach, we found that team identification mediated these relationships. Thus, high-quality peer leaders succeeded in creating a shared sense of ‘us’ in the team, and this team identification in turn generated all the positive outcomes. To conclude, by sharing their lead and empowering the peer leaders in their team, formal leaders are key drivers of the team’s effectiveness, while also enhancing team members’ health and well-being.